Wise Use of Technology : Fostering IMTAQ and IPTEK in The Pesantren Region of Cianjur Regency, West Java - Sauri, Sofyan; Maulani, Hikmah; Saleh, nalahuddin; Khalid, Shofa Musthofa; Tantowi, Yusuf Ali; Sanusi, Anwar (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to foster IMTAQ (Faith and Piety) and IPTEK (Science and Technology) in the pesantren (Islamic boarding school) region of Cianjur Regency, West Java. The focus of the community service is on how pesantren can integrate modern technology to strengthen religious and academic education. The methods applied in this service involved a participatory approach and collaboration with relevant parties. The results showed that the integration of technology in pesantren not only improves the quality of learning but also facilitates the balanced development of student's character in both IMTAQ and IPTEK. This study highlighted the importance of training and capacity building for educators and the need for policies that support the wise use of technology in the pesantren environment. The community service had successfully demonstrated the transformative potential of integrating faith-based education with modern technological advancements. Through a series of targeted interventions and collaborative efforts, the project achieved several significant outcomes. Thus, pesantren can become a model of education that combines traditional values with technological advancements to produce a generation that is both religious and knowledgeable.